2013
DOI: 10.1542/peds.2012-1628
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Salt Intake, Sugar-Sweetened Beverage Consumption, and Obesity Risk

Abstract: OBJECTIVE: To determine the association among dietary salt, fluid, and sugar-sweetened beverage (SSB) consumption and weight status in a nationally representative sample of Australian children aged 2 to 16 years. METHODS: Cross-sectional data from the 2007 Australian National Children’s Nutrition and Physical Activity Survey. Consumption of dietary salt, fluid, and SSB was determined via two 24-hour dietary recalls. BMI was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
160
6
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(197 citation statements)
references
References 38 publications
(48 reference statements)
14
160
6
14
Order By: Relevance
“…28 In humans, greater sodium consumption has been linked to higher body weight, 3,4 possibly due to sodium' s effect on fluid intake because high sodium intake is often accompanied by high consumption of energy-dense foods and sugar-sweetened soft drinks. [5][6][7][8][9] By contrast, we showed that higher sodium intake was positively associated with several adiposity measures independent of intakes of energy and sweetened soft drinks, which echoes the recent findings in European children and adolescents. Libuda et al reported that a high intake of processed salty foods was associated with higher body weight status independent of energy intake and soft drink consumption.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…28 In humans, greater sodium consumption has been linked to higher body weight, 3,4 possibly due to sodium' s effect on fluid intake because high sodium intake is often accompanied by high consumption of energy-dense foods and sugar-sweetened soft drinks. [5][6][7][8][9] By contrast, we showed that higher sodium intake was positively associated with several adiposity measures independent of intakes of energy and sweetened soft drinks, which echoes the recent findings in European children and adolescents. Libuda et al reported that a high intake of processed salty foods was associated with higher body weight status independent of energy intake and soft drink consumption.…”
Section: Discussionsupporting
confidence: 87%
“…1,2 In humans, greater sodium consumption has been linked to higher body weight, 3,4 possibly due to sodium' s effect on fluid intake because high sodium intake is often accompanied by high consumption of energy-dense foods and sugarsweetened soft drinks. [5][6][7][8][9] However, this may not always be the case because other studies have reported a positive relationship between dietary sodium intake and obesity independent of energy intake and sugar-sweetened beverage consumption. [10][11][12][13] This apparent discrepancy may be attributed, in part, to differences in the population studied and the study design and instruments used.…”
mentioning
confidence: 99%
“…(10)(11)(12)(13) Extensive reviews and metaanalyses have also been generated on the link between SSB consumption and weight gain and the bulk of these supports the direct association between SSB consumption and obesity, including the most recent meta-analysis. (14) SSB consumption can also, directly or indirectly, promote the onset of hypertension, (15)(16)(17)(18) dyslipidemia, (18,19) and impaired glucose tolerance (Figure 1).…”
Section: Scientific Advisory Committee On Nutrition and Americanmentioning
confidence: 99%
“…[33][34][35]. Кроме того, известно, что широ-кое использование сахаросодержащих напитков и про-дуктов фастфуд сопровождается снижением потребления детьми молочных продуктов и овощей [36,37].…”
Section: роль сахара в питании детейunclassified
“…При обследо-вании более 4000 детей в возрасте 2-16 лет была установлена прямая зависимость количества потребля-емой жидкости от содержания соли в рационе: каждый дополнительный 1 г соли повышал объем выпитой жидкости на 46 г/сут (p < 0,001). Эти дети в качестве питья использовали преимущественно сахаросодержа-щие, в том числе газированные, напитки, при этом их потребление в объеме более 250 мл/сут чаще (на 26%) приводило к формированию избыточной массы тела и ожирения [36,60].…”
Section: роль сахара в питании детейunclassified